WAYS TO FORM A HEALTHY LIFESTYLE FOR CHILDREN IN THE FAMILY.: WAYS TO FORM A HEALTHY LIFESTYLE FOR CHILDREN IN THE FAMILY. - xasanov, anvar; Олимов, Алишер (Физическое воспитание, спорт и здоровье, 2022)
The article describes how children form a healthy lifestyle in the family.